Avaliação da Atividade Antioxidante dos Compostos Fenólicos Presentes na Amburana cearensis - Larisse de Oliveira dos Santos; Magda Rosa Reis; Luci Emi Ogava; Katyúscya Veloso Leão; Luciana Lucas Machado; Simone Possedente de Lira (Orbital: The Electronic Journal of Chemistry, 2016)
Amburana cearensis A. C. Smith (Fabaceae) is popularly known as cumaru.  Its stem bark is used in folk medicine for the treatment of respiratory disorders and as anti-inflammatory.  With knowledge of their pharmacological potential of this work was to total phenolics content and antioxidant activity in the ethanolic extract of leaves and bark (EEF and EEC) and methanol and ethyl acetate fractions of leaves (FMEF and FAcF). The Antioxidant activity of the extract and fractions was evaluated using spectrophotometric method at concentrations of 1.0; 0.1; 0.01 and 0.001 mg mL-1. For the total phenolics, determined by the Folin-Ciocalsteu method, expressed as gallic acid equivalent g-1 (GAE) for sample.  All samples showed antioxidant activity, but FMEF fraction showed the highest value for activity (94%) when compared to standard ascorbic acid. The total phenolics content showed the most significant result was to FAcF fraction with 134.66 mg of EGA g-1.DOI: http://dx.doi.org/10.17807/orbital.v1i1.706